Improvement of buffalo bull semen quality through sephadex filtration and subsequent assessment through polyacrylamide gel column migration - SINGH, SATWINDER; PANGAONKAR, G R; CHOUDHARY, K C; VERMA, H K (The Indian Journal of Animal Reproduction, 2023)
To study the effect of sephadex (G 15- 120) filtration in improving the buffalo bull semen quality, 20ejaculates from four bulls exhibiting poor freezability were taken. Sephadex filtered Tris-yolk extended semenexhibited significant(P < 0.05) improvement in sperm motility (63.75 ± 0.99 vs 71 .75 ± 0. 81 percent), live spermcount ( 75.15 ± 0.65 vs 83.00 ± 0.70 percent) and spermatozoa! penetrability through PAG column (20.35 ± 0.26 vs22.43 :t 0.32 mm/20 min.) as compared to unfiltered semen. Subsequently sephadex filtration improved the freezabilityof .semen by increasing (p
Keywords: Buffalo semen quality; Sephadex filtration; freezing of semen; sperm motility